Antenatal sildenafil treatment improves neonatal pulmonary hemodynamics and gas exchange in lambs with diaphragmatic hernia. (4th October 2019) - Kashyap, A. J.; Dekoninck, P. L. J.; Rodgers, K. A.; Thio, M.; Mcgillick, E. V.; Amberg, B. J.; Skinner, S. M.; Moxham, A. M.; Russo, F. M.; Deprest, J. A.; Hooper, S. B.; Crossley, K. J.; et al.
ABSTRACT: Objectives: Infants with congenital diaphragmatic hernia (CDH) are predisposed to pulmonary hypertension after birth, owing to lung hypoplasia that impairs fetal pulmonary vascular development. Antenatal sildenafil treatment attenuates abnormal pulmonary vascular and alveolar development in rabbit and rodent CDH models, but whether this translates to functional improvements after birth remains unknown. We aimed to evaluate the effect of antenatal sildenafil on neonatal pulmonary hemodynamics and lung function in lambs with diaphragmatic hernia (DH). Methods: DH was surgically induced at approximately 80 days' gestation in 16 lamb fetuses (term in lambs is approximately 147 days). From 105 days' gestation, ewes received either sildenafil (0.21 mg/kg/h intravenously) or saline infusion until delivery ( n = 8 fetuses in each group). At approximately 138 days' gestation, all lambs were instrumented and then delivered via Cesarean section. The lambs were ventilated for 120 min with continuous recording of physiological (pulmonary and carotid artery blood flow and pressure; cerebral oxygenation) and ventilatory parameters, and regular assessment of arterial blood gas tensions. Only lambs that survived until delivery and with a confirmed diaphragmatic defect at postmortem examination were included in the analysis; these comprised six DH‐sildenafil lambs and six DH‐saline control lambs. Results: Lung‐to‐body‐weight ratio (0.016 ± 0.001 vs 0.013 ± 0.001; P = 0.06) and dynamic lung compliance (0.8 ± 0.2 vs 0.7 ± 0.2 mL/cmH2 O; P = 0.72) were similar in DH‐sildenafil lambs and controls. Pulmonary vascular resistance decreased following lung aeration to a greater degree in DH‐sildenafil lambs, and was 4‐fold lower by 120 min after cord clamping than in controls (0.6 ± 0.1 vs 2.2 ± 0.6 mmHg/(mL/min); P = 0.002). Pulmonary arterial pressure was also lower (46 ± 2 vs 59 ± 2 mmHg; P = 0.048) and pulmonary blood flow higher (25 ± 3 vs 8 ± 2 mL/min/kg; P = 0.02) in DH‐sildenafil than in DH‐saline lambs at 120 min. Throughout the 120‐min ventilation period, the partial pressure of arterial carbon dioxide tended to be lower in DH‐sildenafil lambs than in controls (63 ± 8 vs 87 ± 8 mmHg; P = 0.057), and there was no significant difference in partial pressure of arterial oxygen between the two groups. Conclusions: Sustained maternal antenatal sildenafil infusion reduced pulmonary arterial pressure and increased pulmonary blood flow in DH lambs for the first 120 min after birth. These findings of improved pulmonary vascular function are consistent with improved pulmonary vascular structure seen in two previous animal models. The data support the rationale for a clinical trial investigating the effect of antenatal sildenafil in reducing the risk of neonatal pulmonary hypertension in infants with CDH. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.